Financial Education: Bibliometic Analysis from 1989 to 2023 - Senduk, Feibry Feronika Wiwenly; Arjanto, Paul (Fakultas Ekonomi Universitas Negeri Manado, 2024)
This study applies a comprehensive bibliometric analysis to financial education research published between 1989 and 2023 with the aim of exploring trends, patterns, and key themes in the field. By collecting data from various Scopus databases, totaling 280 documents, the analysis involves the distribution of publications, identification of influential articles and authors, and exploration of citation and co-occurrence relationships. Visualizing the results using mapping techniques helps depict the structure and dynamics of financial education research during the specified period. Key findings include limited collaboration among authors, uneven contributions across countries, and the emergence of various subfields in the literature. The research implications encompass the necessity for increased collaboration among researchers to address collaboration gaps, providing in-depth insights into the global distribution of research contributions, and offering insights for future research and policy in financial education.